2019
DOI: 10.1002/acm2.12592
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiparametric MRI‐based and transrectal ultrasound‐based preplans with intraoperative ultrasound‐based planning for low dose rate interstitial prostate seed implantation

Abstract: Purpose Transrectal ultrasound images are routinely acquired for low dose rate (LDR) prostate brachytherapy dosimetric preplanning (pTRUS), although diagnostic multiparametric magnetic resonance imaging (mpMRI) may serve this purpose as well. We compared the predictive abilities of TRUS vs MRI relative to intraoperative TRUS (iTRUS) to assess the role of mpMRI in brachytherapy preplanning. Materials and methods Retrospective analysis was performed on 32 patients who underwent iTRUS‐guided prostate LDR brachyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Preplanning TRUS, MRI, and intraoperative TRUS all predicted similar numbers of seeds for implantation. The ability of MRI to consistently and accurately determine prostate volume and predict the required number of seeds equivalently to preplanning TRUS was demonstrated, and the appointment of MRI as the sole imaging modality for LDRPB preplanning was supported (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preplanning TRUS, MRI, and intraoperative TRUS all predicted similar numbers of seeds for implantation. The ability of MRI to consistently and accurately determine prostate volume and predict the required number of seeds equivalently to preplanning TRUS was demonstrated, and the appointment of MRI as the sole imaging modality for LDRPB preplanning was supported (14).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found no significant difference between MRI-and TRUSbased prostate volumes (12), whereas others have (16). Some studies report MRI overestimating prostate volume relative to TRUS, whereas others report MRI underestimating prostate volume relative to TRUS (14).…”
Section: Introductionmentioning
confidence: 99%
“…Brachytherapy preplanning was performed utilizing mpMRI ( 19 ). The mean prostate volume was 35.2 ± 8.1 cc (range, 26.6–53.1cc).…”
Section: Introductionmentioning
confidence: 99%
“…Brachytherapy low-dose-rate (LDR) or highdose-rate (HDR) is a standard primary treatment for low-or intermediate-risk PCa [6]. TRUS-Bx is routinely acquired for LDR prostate brachytherapy preplanning (pTRUS), although diagnostic mpMRI may serve this purpose as well [7]. Fredman et al compared the predictive abilities of TRUS vs. MRI relative to intraoperative TRUS (iTRUS) to assess the role of mpMRI in brachytherapy preplanning.…”
mentioning
confidence: 99%
“…Shaaer et al described the use of mp-MRI during prostate HDR brachytherapy planning [8]. These works suggest that mpMRI carries numerous diagnostic, staging and preplanning advantages that facilitate better patient selection and delivery of novel dose escalation and targeted therapy, with no additional surgical or anesthesia time [7,8].…”
mentioning
confidence: 99%